Avaliação da dinâmica familiar e da sintomatologia psicopatológica em contexto de divórcio - Loureiro, Inês Madalena Rocha (2025)
Divorce is an increasing reality in Portuguese society, bringing significant changes at social, economic, psychological, and legal levels. Despite the potentially disruptive nature of divorce, recent studies highlight the possibility of personal growth and adaptation to new family dynamics. From the perspective of both parents and children, the present quantitative study aims to analyse the relationship between variables related to divorce and family dynamics, namely resilience and family functioning, as well as their relationship with psychopathological symptomatology. To this end, the Walsh Family Resilience Questionnaire (WFRQ), the Systemic Clinical Outcome and Routine Evaluation (SCORE-15), and the Brief Symptom Inventory – 18 (BSI-18) were used. The sample consists of 75 participants, of whom 39 are parents and 36 are children, aged between 19 and 62 years (M = 33.11; SD = 11.78). The results revealed significant correlations between the perception of the quality of family relationships (after divorce) and the WFRQ and SCORE-15 instruments. Significant correlations were also identified between the perception of the quality of family relationships (after divorce) and the perceived difficulties in the divorce process and the BSI-18 results. Additionally, both family resilience and family functioning were significantly correlated with psychological distress. Finally, significant differences were found between parents' and children's perceptions regarding family functioning. These findings suggest that the perception of divorce influences family dynamics and psychological well-being, highlighting the importance of considering resilience factors in the family's adaptation to divorce. This study contributes to a deeper understanding of the impact of divorce on both parents and children, encouraging future research in this area.